STRUCTURAL PARALYSIS OF INTERNAL OVERSIGHT AND THE ABUSE OF ADMINISTRATIVE DISCRETION IN INDONESIA LOCAL GOVERNMENT - Rohmad Pujiyanto; Deny Puspitasari (University Of Bengkulu Law Journal, 2026)
This study analyzes the pathology of administrative discretion in Indonesian local government, focusing on cases of "job-selling" and procurement maladministration identified in 2026. Despite the legal framework provided by Law No. 30 of 2014, administrative discretion (freies ermessen) remains vulnerable to systemic abuse by regional heads. Using a normative-legal research method with statutory, case, and conceptual approaches, this research examines how the erosion of meritocracy and the manipulation of public contracts occur within a weakened oversight environment. The findings reveal that the internal oversight body (APIP) suffers from structural paralysis due to its jurisdictional subordination to the very authority it is tasked to monitor. This creates a "control vacuum" that allows administrative corruption to persist despite digital governance reforms. This study proposes a radical legal reconstruction by transforming APIP into a vertically independent institution and establishing rigid, objective parameters for administrative discretion through "Administrative Impact Assessments." By strengthening these preventive instruments, the administrative law framework can effectively mitigate bureaucratic capture and restore institutional integrity in local governance.